2020
DOI: 10.1111/vec.12974
|View full text |Cite
|
Sign up to set email alerts
|

Cataloguing the response by emergency veterinary hospitals during the COVID‐19 pandemic via weekly surveys

Abstract: Background The COVID‐19 pandemic has presented veterinary emergency hospitals with unique challenges. Rapid online surveys represent an efficient way of collating responses to rapidly shifting circumstances. Methods Fifty, 24‐h small animal emergency veterinary hospital representatives were recruited to participate in weekly surveys in April 2020 to catalog changes due to COVID‐19 pandemic. Key findings The majority of emergency veterinary ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 3 publications
(2 reference statements)
4
24
0
Order By: Relevance
“…In the free-text comments, respondents reported struggling with determining what counted as an essential or emergent case -likely exacerbated by the absence of an end-date for pandemic-associated restrictions, and variation in official guidance and multiple waves of SARS-CoV-2 infection. This finding aligns with that of Wayne and Rozanski, who found variation in services that US-based veterinary hospitals would provide during the pandemic (23). Similarly, a roundtable discussion on how the COVID-19 pandemic impacted the practice of avian and companion animal veterinary medicine revealed variation in both what was considered an essential service, and the safest way for veterinary hospitals to provide services (12).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In the free-text comments, respondents reported struggling with determining what counted as an essential or emergent case -likely exacerbated by the absence of an end-date for pandemic-associated restrictions, and variation in official guidance and multiple waves of SARS-CoV-2 infection. This finding aligns with that of Wayne and Rozanski, who found variation in services that US-based veterinary hospitals would provide during the pandemic (23). Similarly, a roundtable discussion on how the COVID-19 pandemic impacted the practice of avian and companion animal veterinary medicine revealed variation in both what was considered an essential service, and the safest way for veterinary hospitals to provide services (12).…”
Section: Discussionsupporting
confidence: 83%
“…In the context of a global pandemic, the number of financially limited clients encountered by any one veterinary team member may become overwhelming, with fewer opportunities to work within cost constraints, recognition that clients who have lost jobs due to the pandemic are not responsible for their financial limitations, or a combination of these. In the US, 72% of small animal emergency hospitals reported that clients had more financial limitations than prior to the pandemic (23). It is likely that the longterm economic impacts of COVID-19, particularly large-scale unemployment (24), will decrease the accessibility of veterinary care for many people, compromising animal health and welfare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously shared information gathered from survey data in April 2020. 1 We have continued to survey emergency veterinary hospitals and share some updates from sur- In summary, increased caseload and burnout seem to be the biggest challenges for emergency veterinary hospitals during the COVID-19 pandemic, coupled with the unpredictable future. Ongoing support of team members and among the emergency/critical care community is vital, and we plan to continue surveys and data dissemination.…”
Section: The Evolving Response By Emergency Veterinary Hospitals Durimentioning
confidence: 99%
“…The effect of COVID‐19 outbreak on veterinary service provision has been unprecedented. The adjustment of service provision to the crisis has been unavoidable 1 . The effect of COVID‐19 pandemic on veterinary practice has not been yet well described in the literature.…”
mentioning
confidence: 99%